Penerapan Model Pembelajaran Kooperatif Tipe Think Pair Square terhadap Kemampuan Matematis dan Aktivitas Belajar Peserta Didik Kelas VIII SMP Negeri 3 Padang Panjang. - DIAN NOVITRI YANTI (Departemen Matematika, 2019)
A mathematical communication ability is a skills that must be own by the student’s. However, based on the results of tests that have done in SMPN 3 Padang Panjang it still low and centered teacher learning. This can be improved by applying the cooperative type Thiink Pair Square learning model so it makes the student’s become active in the learning process. The purpose of this research are to know and describes whether the ability of mathematical communication skills of the student’s of the experimental class is better than the control class and to know how is the learning activities of the students by applying to Think Pair Square learning models. This type of this research is a combination of quasy experiment and descriptive research with a static group design research design. Based on the results of the research it can be concluded that the activities of the students that learn with the cooperative learning model think pair square tend to increase and mathematical communication ability of students that learn by think pair square is better than the student’s who learn by conventional learning.Keywords – Mathematical Communication Skiils, Learning Activity, Think Pair Square Learning’s Model